Doxorubicin as an antioxidant: Maintenance of myocardial levels of lycopene under doxorubicin treatment - Ferreira, Ana Lúcia dos Anjos [UNESP]; Yeum, Kyung-Jin; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Corrêa, Camila Renata [UNESP]; Pereira, Elenize Jamas; Russell, Robert Mitchell; Krinsky, Norman I.; Tang, Guangwen (Elsevier B.V., 2007)
The mechanism of doxorubicin-induced cardiotoxicity remains controversial. Wistar rats (n=96) were randomly assigned to a control (C), lycopene (L), doxorubicin (D), or doxorubicin+lycopene (DL) group. The L and DL groups received lycopene (5 mg/kg body wt/day by gavage) for 7 weeks. The D and DL groups received doxombicin (4 mg/kg body wt intraperitoneally) at 3, 4, 5, and 6 weeks and were killed at 7 weeks for analyses. Myocardial tissue lycopene levels and total antioxidant performance (TAP) were analyzed by HPLC and fluorometry, respectively. Lycopene metabolism was determined by incubating H-2(10)-lycopene with intestinal mucosa postmitochondrial fraction and lipoxygenase and analyzed with HPLC and APCI mass spectroscopy. Myocardial tissue lycopene levels in DL and L were similar. TAP adjusted for tissue protein were higher in myocardium of D than those of C (P=0.002). Lycopene metabolism study identified a lower oxidative cleavage of lycopene in D as compared to those of C. Our results showed that lycopene was not depleted in myocardium of lycopene-supplemented rats treated with doxorubicin and that higher antioxidant capacity in myocardium and less oxidative cleavage of lycopene in intestinal mucosa of doxorubicin-treated rats suggest an antioxidant role of doxombicin rather than acting as a prooxidant. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: lycopene; doxorubicin; heart; rat; enzymatic cleavage; oxidative cleavage; antioxidant capacity